2017
DOI: 10.1371/journal.pone.0176590
|View full text |Cite
|
Sign up to set email alerts
|

Combined Red Clover isoflavones and probiotics potently reduce menopausal vasomotor symptoms

Abstract: BackgroundNatural estrogen decline leads to vasomotor symptoms (VMS). Hormone therapy alleviates symptoms but increases cancer risk. Effective treatments against VMS with minimal cancer risks are needed. We investigate the effects of a highly bioavailable aglycone rich Red Clover isoflavone treatment to alleviate existing menopausal VMS, assessed for the first time by 24hour ambulatory skin conductance (SC)Methods and resultsWe conducted a parallel, double blind, randomised control trial of 62 peri-menopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 51 publications
(48 reference statements)
2
51
0
1
Order By: Relevance
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%
“…Other subjective vasomotor symptoms measurement tools included a 20‐item structured symptom checklist; two of the items asking about the presence of hot flushes and cold/night sweats, a 5‐point (from none to very severe) scoring system about the severity of hot flushes and night sweats, Interactive Voice Response System to record the number and severity of the hot flushes, and self‐reported surveys . Objective measures of vasomotor symptoms such as skin conductance were used in five trials in addition to subjective measures (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Peri-menopausal women subjects were supplemented with isoflavones and probiotics (34 mg/d isoflavones; probiotic combinations and dosage were not revealed in the study) for 12 w. The hot flush frequency (HFF), hot flush intensity, selfreported HFF, and hot flush severity, plasma lipids and blood pressure were measured. The results suggested that moderate intervention of red clover isoflavone and probiotics significantly reduced the self-reported vasomotor symptoms [44]. 9 CFU of L. crispatus LbV 88, 1 × 10 9 CFU of L. rhamnosus LbV 96, 0.2 × 10 9 CFU of L. ensenii LbV 116 and 0.3 × 10 9 CFU of L. gasseri LbV 150N) twice daily for two weeks.…”
Section: Probiotics and Menopausementioning
confidence: 92%
“…Red clover can also reduce the intensity of other complaints from this period, but future studies are necessary in order to confirm the current knowledge [21]. Lambert et al suggested that red clover was more useful and also was superior to placebo in decreasing selfreported vasomotor disorders [30].…”
Section: The Management Of Vasomotor Disordersmentioning
confidence: 99%